2008
DOI: 10.5194/angeo-26-4031-2008
|View full text |Cite
|
Sign up to set email alerts
|

Solar wind control of plasma number density in the near-Earth plasma sheet: three-dimensional structure

Abstract: Abstract. The plasma number density in the near-Earth plasma sheet depends on the solar wind number density and the north-south component of interplanetary magnetic field (IMF B z ) with time lag and duration of several hours. We examined the three-dimensional structure of such dependences by fitting observations of plasma sheet and solar wind to an empirical model equation. Analyses were conducted separately for northward and southward IMF conditions. Effects of solar wind speed and IMF orientation were also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
17
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 36 publications
6
17
0
Order By: Relevance
“…In the dense region the magnetosheath plasma flowed tailward with a speed of $ 2002290 km s À1 , while flows were stagnant or slightly sunward on the magnetospheric side, which shows the presence of velocity shear similar in magnitude to that on the dawn side. The magnetospheric plasma temperature on both sides was as low as 10-15 MK, which is much higher than the magnetosheath temperature but is lower than the typical magnetosphere temperature (several tens of MK), and the magnetospheric ion density on both sides ð $ 1 cm À3 Þ was much higher than its usual value ð $ 0:220:4 cm À3 Þ (Nagata et al, 2008). Because both Cluster and GT had opportunities to repeat encounters with the boundary layer ( Fig.…”
Section: Symmetrical Development Of Vorticesmentioning
confidence: 95%
“…In the dense region the magnetosheath plasma flowed tailward with a speed of $ 2002290 km s À1 , while flows were stagnant or slightly sunward on the magnetospheric side, which shows the presence of velocity shear similar in magnitude to that on the dawn side. The magnetospheric plasma temperature on both sides was as low as 10-15 MK, which is much higher than the magnetosheath temperature but is lower than the typical magnetosphere temperature (several tens of MK), and the magnetospheric ion density on both sides ð $ 1 cm À3 Þ was much higher than its usual value ð $ 0:220:4 cm À3 Þ (Nagata et al, 2008). Because both Cluster and GT had opportunities to repeat encounters with the boundary layer ( Fig.…”
Section: Symmetrical Development Of Vorticesmentioning
confidence: 95%
“…Densities vary between about 0.05 and 0.3, mainly below 0.2 cm −3 . These densities are rather low, since typical densities close to the PS flanks are 0.2-0.5 cm −3 (Tsyganenko and Mukai, 2003;Nagata et al, 2008). However, several SW parameters affect the densities in the geomagnetic tail: IMF polarity, solar wind speed and density.…”
Section: Magnetospheric Observationsmentioning
confidence: 99%
“…It was shown that the values of the eddy-diffusion coefficient increase significantly during the growth and expansion phases, being more pronounced in the later. The turbulent transport in the plasma sheet is also affected by the orientation of the interplanetary magnetic field (IMF) (Nagata et al, 2008;Wang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%